Implementasi Sistem Monitoring Tanah dan Pengendalian Hama untuk Meningkatkan Produktivitas Pertanian Hortikultura di Kelompok Tani Tunas Muda Wonosobo Jawa Tengah: Penelitian - Wardhana, Alex Sandria Jaya; Damarwan, Eko Swi; Latifa, Annisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Horticultural farming in Indonesia faces recurring pest attacks and declining soil fertility, which lower productivity. This study implemented an 8-in-1 sensor-based soil monitoring system and pest control using solar-powered UV traps at the Tunas Muda Farmers Group in Wonosobo, Central Java, which cultivates potatoes, cabbage, and carrots. Despite its ideal geographical conditions, productivity is still constrained by technical factors. A quantitative method with an experimental design compared land conditions before and after the technology implementation, with data collected through mobile-based IoT sensors. Results showed that the soil monitoring system increased fertilizer efficiency by 35%, while the UV traps reduced pest populations by 42% and chemical pesticide use by 45%. This research contributes to the development of environmentally friendly horticultural smart farming in Indonesia, particularly in the highlands.